Dysfunctional uterine bleeding - Ludmir Grimberg, Abraham (2015)
According to general consensus, today it is defined as abnormal bleeding is not dependent detectable organic cause with conventional methods, it is the loss of menstrual pattern where inflammatory problems is discarded, neoplastic, pregnancy or systemic disease although it can coexist with an organic process.